DnaJ (hsp40) of Streptococcus pneumoniae is involved in bacterial virulence and elicits a strong natural immune reaction via PI3K/JNK. (March 2017) - Cui, Jin; Ma, Chenyu; Ye, Guo; Shi, Yong; Xu, Wenchun; Zhong, Liang; Wang, Jian; Yin, Yibing; Zhang, Xuemei; Wang, Hong
Highlights: DnaJ deficiency affected the virulence and adherence of S. pneumoniae . DnaJ involved in the pneumococcus-induced innate immune response in mice. DnaJ induced the dose- and time-dependent IL-6 production in RAW264.7 cells. DnaJ activated PI3K/JNK signal pathways to induce IL-6 release of RAW264.7 cells. Abstract: As a heat shock protein, DnaJ plays an important role in the pathogenesis of pneumococcal infection. However, how the virulence factor-DnaJ elicits host natural immunity still remains unclear. In this study, we investigated the effects of dnaJ deficiency in Streptococcus pneumoniae ( S. pneumoniae ) on bacterial virulence, and further explored the related molecular mechanisms in vivo and in vitro . By generating dnaJ deficient mutant (Δ dnaJ ), the virulence and colonization were detected in murine pneumonia and sepsis models in vivo . Compared with wild-type parent strain, the abilities of rapid colonization and induction of inflammatory responses of Δ dnaJ in mouse lungs were significantly impaired. Simultaneously, recombinant DnaJ purified from E. coli expression system (rDnaJ) induced macrophage strain RAW264.7 to secrete IL-6 by activation of PI3K and JNK signal pathways, which were confirmed by the specific signaling inhibitors. In conclusion, DnaJ, a novel virulence protein, was essential for the virulence and colonization of S. pneumoniae and induced pro-inflammatory cytokine production in macrophages through PI3K/JNK.